Efficacy and safety of adjuvant curcumin therapy in ulcerative colitis: A systematic review and meta-analysis. (10th May 2022) - Yin, Juntao; Wei, Lunshou; Wang, Naiqin; Li, Xiumin; Miao, Mingsan
Abstract: Ethnopharmacological relevance: Curcumin, an active polyphenol extracted from Traditional Chinese medicine Curcuma longa (turmeric), has shown many health-related benefits and pharmacological effects. Adjuvant curcumin therapy for ulcerative colitis has become increasingly popular, but its efficacy and safety of which is still controversial. The purpose of this study is to evaluate the efficacy and safety of adjuvant curcumin therapy in ulcerative colitis. Materials and methods: The Medline, EMBASE, the Cochrane Library, CNKI, VIP, WanFang, and SinoMed databases were searched from inception to June 2021, to identify all randomized controlled clinical trials with adjuvant curcumin therapy in ulcerative colitis. The primary outcomes were clinical and endoscopic remission, and subgroup analyses were also performed. Results: Six randomized trials with a total of 385 participants were included in this study. Qualified trials recommended that adjuvant curcumin therapy for ulcerative colitis was effective in inducing clinical remission (RR = 2.10, 95% CI 1.13 to 3.89), but not in clinical improvement (RR = 1.62, 95% CI 1.00 to 2.61), endoscopic remission (RR = 4.17, 95% CI 0.63 to 27.71) or endoscopic improvement (RR = 4.13, 95% CI 0.20 to 87.07). Included studies showed that appropriate dosage, formation, longer duration, and topical medication may have a greater potential advantage. No severe adverse effects had been reported. Conclusions: Available evidence suggested that adjuvant curcumin therapy may be effective for clinical remission in ulcerative colitis patients without causing severe adverse effects. The appropriate methods of administration can achieve better curative effect, which requires further study to verify. Graphical abstract: Image 1